The Influence of the Inquiry Learning Model Based on the Quizizz Application on the Learning Outcomes of Class IV Students of State Elementary School 064022 Medan Tuntungan - Marissa Sibuea, Devi; Janson Silaban, Patri; Florentina Ambarwati, Nova; Sipayung, Regina; Lumbangaol, Rumiris (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This research aims to determine the effect of the Inquiry Learning learning model based on the Quizizz application on the learning outcomes of class IV students at SD Negeri 064022 Medan Tuntungan for the 2023/2024 academic year. This type of research is quantitative using experimental methods. The population of this research was class IV students at SD Negeri 064022 Medan Tuntungan, totaling 29 students. Sampling was taken using probability sampling techniques and was obtained from class IV, totaling 29 students. The results of this research show that student learning outcomes are in the very good category with an average of 81.1. The results of this research show that the correlation test results can be seen that the correlation coefficient is 0.816, meaning rcount (0.816) ≥ rtable (0.367), so ha is accepted. So there is a very strong influence between the Inquiry Learning model based on the Quizizz application on the learning outcomes of class IV students at SD Negeri 064022 Medan Tuntungan. It can also be seen from the t-test where tcount ≥ ttable, namely 7.328 ≥ 2.045, thus stating that ha is accepted. This shows that there is a significant positive influence from using the Inquiry Learning model based on the Quizizz application on the learning outcomes of class IV students at SD Negeri 064022 Medan Tuntungan for the 2023/2024 academic year.